2021
DOI: 10.1126/science.abe0290
|View full text |Cite
|
Sign up to set email alerts
|

The missing ocean plastic sink: Gone with the rivers

Abstract: Plastic floating at the ocean surface, estimated at tens to hundreds of thousands of metric tons, represents only a small fraction of the estimated several million metric tons annually discharged by rivers. Such an imbalance promoted the search for a missing plastic sink that could explain the rapid removal of river-sourced plastics from the ocean surface. On the basis of an in-depth statistical reanalysis of updated data on microplastics—a size fraction for which both ocean and river sampling rely on equal te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
136
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(144 citation statements)
references
References 91 publications
4
136
0
4
Order By: Relevance
“…Their reanalysis results in the average residence time of MPs at the ocean surface increasing from days to years, which they suggests strongly reduces "the theoretical need for a missing sink" [40], an observation that is also consistent with Pabortsava and Lampitt [36]. Nevertheless, Weiss et al [40] acknowledge that their estimates are based on underlying data that contain significant uncertainties, but that their observations are perceived to be better aligned with an understanding that surface oceanic MP stocks, particularly within oceanic gyres, result from slow accumulation processes, an observation that is inconsistent with suggestions that there exists relatively rapid environmental fate processes that might help to sequester surface oceanic MPs. An additional notable observation from Wiess et al [40] relates to differences in the properties of MPs between those observed in rivers and those in accumulation areas, whereby the observed differences are suggested to potentially represent a selective sequestration of smaller size MPs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their reanalysis results in the average residence time of MPs at the ocean surface increasing from days to years, which they suggests strongly reduces "the theoretical need for a missing sink" [40], an observation that is also consistent with Pabortsava and Lampitt [36]. Nevertheless, Weiss et al [40] acknowledge that their estimates are based on underlying data that contain significant uncertainties, but that their observations are perceived to be better aligned with an understanding that surface oceanic MP stocks, particularly within oceanic gyres, result from slow accumulation processes, an observation that is inconsistent with suggestions that there exists relatively rapid environmental fate processes that might help to sequester surface oceanic MPs. An additional notable observation from Wiess et al [40] relates to differences in the properties of MPs between those observed in rivers and those in accumulation areas, whereby the observed differences are suggested to potentially represent a selective sequestration of smaller size MPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there continues to be a debate regarding the relative importance of the various processes with respect to the environmental fate and transport of MPs, which results in varying interpretations of data presented throughout the literature. Most recently, Wiess et al [40] provide a statistical re-analysis based on updated data on MPs, the output of which suggests that previous estimates of river fluxes potentially represent overestimates, of up to three-orders of magnitude. Their reanalysis results in the average residence time of MPs at the ocean surface increasing from days to years, which they suggests strongly reduces "the theoretical need for a missing sink" [40], an observation that is also consistent with Pabortsava and Lampitt [36].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations